Vietnam integrated national operational program for avian and human influenza (OPI) 2006 - 2010 (The World Bank, 2006)
The Green book identifies and outlines activities envisaged by the government to achieve the objectives and outputs identified in the integrated National Plan for Avian Influenza Control and Human Pandemic Influenza Preparedness and Response.